2020
DOI: 10.1111/dme.14328
|View full text |Cite
|
Sign up to set email alerts
|

Guidance on the management of Diabetic Ketoacidosis in the exceptional circumstances of the COVID‐19 pandemic

Abstract: We hope that most teams will not find it necessary to use the subcutaneous insulin route to manage DKA, but we understand that this regimen has been welcomed by some working in less well-resourced countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 5 publications
1
47
0
2
Order By: Relevance
“…The association between Covid-19 and hyperglycemia in elderly patients with T2D ( 60 ) seems likely to reflect metabolic inflammation and exaggerated cytokine release. Strikingly, recent data suggest that SARS-CoV2 infection can lead to a deterioration in glycemic control, involving both profound insulin resistance (requiring as much as 50–100 U insulin/h) and impaired insulin secretion, together leading to diabetic ketoacidosis, DKA ( 61 , 62 ). Thus, frequent cases of severe DKA have been observed on admission to hospital of patients with Covid-19 ( 14 ) and contribute to mortality and morbidity ( 9 ).…”
Section: Covid-19 and Diabetes: A Vicious Circle?mentioning
confidence: 99%
“…The association between Covid-19 and hyperglycemia in elderly patients with T2D ( 60 ) seems likely to reflect metabolic inflammation and exaggerated cytokine release. Strikingly, recent data suggest that SARS-CoV2 infection can lead to a deterioration in glycemic control, involving both profound insulin resistance (requiring as much as 50–100 U insulin/h) and impaired insulin secretion, together leading to diabetic ketoacidosis, DKA ( 61 , 62 ). Thus, frequent cases of severe DKA have been observed on admission to hospital of patients with Covid-19 ( 14 ) and contribute to mortality and morbidity ( 9 ).…”
Section: Covid-19 and Diabetes: A Vicious Circle?mentioning
confidence: 99%
“…Type 1 Diabetes Mellitus and Diabetic ketoacidosis One study reported that a large number of patients with COVID-19 developed diabetic ketoacidosis (DKA), hyperosmolar hyperglycaemic state (HHS) or a combination of both [29]. It has also been found that COVID-19 may mask the symptoms of DKA [30].…”
Section: Special Situationsmentioning
confidence: 99%
“…In large case series, COPD was present in only 11% in China, 1 5% in the United States 2 and 18% in the UK 3 ; but, by contrast, diabetes was present in 8%, 1 33.8% 2 and 21% 3 of cases, respectively. In addition, marked insulin resistance with ketosis has been reported, 4,5 even in those individuals with no preceding history of diabetes 5,6 …”
mentioning
confidence: 99%